Eigenstrain boundary layer modelling of the yttria-partially stabilised zirconia–porcelain interface in dental prostheses - Lunt, AJG; Korsunsky, AM (Elsevier, 2020)
The exceptional strength and appealing aesthetics of porcelain veneered yttria partially stabilised zirconia (YPSZ) dental prostheses, has led to the widespread adoption of these materials. However, near-interface chipping of the porcelain remains the primary failure mode. Advanced experimental techniques have recently revealed significant variations in residual stress and YPSZ phase distribution at the YPSZ–porcelain interface. Therefore, in order to improve existing understanding and effectively optimise the production of these devices, an enhanced model of the YPSZ coping that includes these newly discovered phenomena is presented in this study.